Towards a comprehensive characterisation of the human internal chemical exposome: Challenges and perspectives - David, Arthur; Chaker, Jade; Price, Elliott J; Bessonneau, Vincent; Chetwynd, Andrew J; Vitale, Chiara M; Klánová, Jana; Walker, Douglas I; Antignac, Jean-Philippe; Barouki, Robert; Miller, Gary W (Environment international, 2021)
The holistic characterisation of the human internal chemical exposome using high-resolution mass spectrometry (HRMS) would be a step forward to investigate the environmental ætiology of chronic diseases with an unprecedented precision. HRMS-based methods are currently operational to reproducibly profile thousands of endogenous metabolites as well as externally-derived chemicals and their biotransformation products in a large number of biological samples from human cohorts. These approaches provide a solid ground for the discovery of unrecognised biomarkers of exposure and metabolic effects associated with many chronic diseases. Nevertheless, some limitations remain and have to be overcome so that chemical exposomics can provide unbiased detection of chemical exposures affecting disease susceptibility in epidemiological studies. Some of these limitations include (i) the lack of versatility of analytical techniques to capture the wide diversity of chemicals; (ii) the lack of analytical sensitivity that prevents the detection of exogenous (and endogenous) chemicals occurring at (ultra) trace levels from restricted sample amounts, and (iii) the lack of automation of the annotation/identification process. In this article, we discuss a number of technological and methodological limitations hindering applications of HRMS-based methods and propose initial steps to push towards a more comprehensive characterisation of the internal chemical exposome. We also discuss other challenges including the need for harmonisation and the difficulty inherent in assessing the dynamic nature of the internal chemical exposome, as well as the need for establishing a strong international collaboration, high level networking, and sustainable research infrastructure. A great amount of research, technological development and innovative bio-informatics tools are still needed to profile and characterise the "invisible" (not profiled), "hidden" (not detected) and "dark" (not annotated) components of the internal chemical exposome and concerted efforts across numerous research fields are paramount.
Keywords: Environmental Exposure; Internal chemical exposome; Exposome; Non-targeted analysis; hmotnostní spektrometrie; expozom; biologické markery; High-Resolution Mass Spectrometry; lidé; Mass Spectrometry; Suspect screening; Humans; Biomarkers; vystavení vlivu životního prostředí; EWAS